GRK2 kinases in the primary cilium initiate SMOOTHENED-PKA signaling in the Hedgehog cascade. - Madison F Walker; Jingyi Zhang; William Steiner; Pei-I Ku; Ju-Fen Zhu; Zachary Michaelson; Yu-Chen Yen; Annabel Lee; Alyssa B Long; Mattie J Casey; Abhishek Poddar; Isaac B Nelson; et al. (PLoS Biology)
During Hedgehog (Hh) signal transduction in development and disease, the atypical G protein-coupled receptor (GPCR) SMOOTHENED (SMO) communicates with GLI transcription factors by binding the protein kinase A catalytic subunit (PKA-C) and physically blocking its enzymatic activity. Here, we show that GPCR kinase 2 (GRK2) orchestrates this process during endogenous mouse and zebrafish Hh pathway activation in the primary cilium. Upon SMO activation, GRK2 rapidly relocalizes from the ciliary base to the shaft, triggering SMO phosphorylation and PKA-C interaction. Reconstitution studies reveal that GRK2 phosphorylation enables active SMO to bind PKA-C directly. Lastly, the SMO-GRK2-PKA pathway underlies Hh signal transduction in a range of cellular and in vivo models. Thus, GRK2 phosphorylation of ciliary SMO and the ensuing PKA-C binding and inactivation are critical initiating events for the intracellular steps in Hh signaling. More broadly, our study suggests an expanded role for GRKs in enabling direct GPCR interactions with diverse intracellular effectors.